From two heads to one: The short-run effects of the recentralization of political power in rural China - Olivier Marie; Thomas Post; Zihan Ye; Xiaopeng Zou (Tinbergen Institute, 2024)
The consequences of granting democratic rights to citizens in otherwise authoritarian regimes has been extensively studied. Much less is know about the implications of retracting these rights when a government wants to recentralize power. Autonomous governance in rural China, introduced in the 1980s, has declined over the past two decades. In 2018, the Communist Party promoted a "one head" policy, replacing the dual governance of village chief and party secretary with a single office-holder. We examine the short-term impacts of this policy on voting behavior and political perceptions using a nationally representative survey and election timing as an instrument. Our findings reveal a significant decrease in election turnout in "one head" villages due to reduced competition. However, villagers' perceptions improve: they report less corruption and greater confidence in local government. This suggests that recentralization was achieved at the cost of electoral involvment but without negative backlash on institutional quality perceptions.
Keywords: D72; D73; H77; P3; R28; 330; Recentralization; dual office-holding; election turnout; political perceptions; rural China